Development of a braided electrospun suture to augment tendon repairs - Abhari, RE (2019)
Tendon tears are common and often require surgical repair. However, many surgical repairs fail, despite continued advances in surgical materials and techniques. Rotator cuff surgery, the clinical focus of this thesis, has particularly poor outcomes. Repair failure can be partially attributed to the inappropriate repurposing of sutures from use in other tissues, which fail to integrate with the specialised tendon tissue.